Survey of ICT and Education in Africa : Côte D’Ivoire Country Report - Fall, Babacar (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev) - supported survey of the Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. The development of ICT in Ivorian colleges, universities and teaching institutions is expected to revive distance training, the exchange of training programs relating to technology, improve access to computer equipment, and play a leading role in a more large-scale and efficient integration of ICT in the education system. The main challenges to the use of ICTs in education in Côte d'Ivoire are the lack of necessary infrastructure, computer equipment, qualified human resources, and the high cost of ICT materials. Large disparities in access to equitable educational opportunities between genders, ethnicities, and regions needs are to be remedied. Despite these obstacles, the gradual adoption of training programs, public and private initiatives, and other activities are contributing to the achievement of a realistic vision.